Advanced synchrotron micro characterization of laser post-processed plasma sprayed LLZO solid-state battery electrolyte - Hasani, Arman; Joshi, Shrikant; Salminen, Antti; Goel, Sneha; Breard, Antonin; Juan, Mathias; Grazyna Makowska, Malgorzata; Makila, Ermei; Nayak, Chinmayee; Ganvir, Ashish (United Kingdom, 2026)
Garnet-type solid-state electrolytes such as Li7La3Zr2O12 (LLZO) offer high ionic conductivity but present challenges in scalable processing due to phase instability and poor interfacial contact. In this study, LLZO thin-film coatings were fabricated via suspension plasma spraying (SPS) and subjected to laser-based thermal post-processing to improve surface and microstructural properties. Synchrotron micro-XRD, along with SEM, EDS, and surface profilometry was employed to analyze the effects of laser post-processing. Results reveal that laser processing reduced surface roughness by up to nearly 40%, eliminated the La(OH)3 phase which is known to increase interfacial resistance, and led to the formation of Li2ZrO3 and Li2CO3 due to localized remelting. These findings highlight the dual role of laser post-processing in improving both morphological and chemical characteristics of SPS LLZO, offering a promising strategy to enhance solid electrode-solid electrolyte interface quality in solid-state battery architectures.
20th Nordic Laser Materials Processing Conference